Mitochondrial Stress Signalling: HTRA2 and Parkinson's Disease - Enrico Desideri; L. Miguel Martins (International Journal of Cell Biology)
Mitochondria are cellular energy generators whose activity requires a continuous supply of oxygen. Recent genetic analysis has suggested that defects in mitochondrial quality control may be key factors in the development of Parkinson’s disease (PD). Mitochondria have a crucial role in supplying energy to the brain, and their deterioration can affect the function and viability of neurons, contributing to neurodegeneration. These organelles can sow the seeds of their own demise because they generate damaging oxygen-free radicals as a byproduct of their intrinsic physiological functions. Mitochondria have therefore evolved specific molecular quality control mechanisms to compensate for the action of damaging agents such as oxygen-free radicals. PTEN-induced putative kinase 1 (PINK1) and high-temperature-regulated A2 (HTRA2), a mitochondrial protease, have recently been proposed to be key modulators of mitochondrial molecular quality control. Here, we review some of the most recent advances in our understanding of mitochondria stress-control pathways, focusing on how signalling by the p38 stress kinase pathway may regulate mitochondrial stress by modulating the activity of HTRA2 via PINK1 and cyclin-dependent kinase 5 (CDK5). We also propose how defects in this pathway may contribute to PD.